2009
DOI: 10.1080/08990220902738243
|View full text |Cite
|
Sign up to set email alerts
|

Perception and suppression of thermally induced pain: A fMRI study

Abstract: Two neuroimaging studies using functional magnetic resonance imaging (fMRI) and thermally induced pain are presented. Fifteen healthy right-handed subjects were imaged while they had to discern different levels of thermal stimuli in the first study and while they disengaged from the feeling of pain during constant stimulation in the second study. In the first experiment, during painful phasic stimuli, right-sided anterior insular activation as well as bilateral posterior insular activation could be shown regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 58 publications
3
77
1
1
Order By: Relevance
“…44 Another recent fMRI study also reported significant activations in several cortical and subcortical regions when a high-pain cold stimulus was applied to the thenar surface of the right hand. The activated regions included, but were not limited to, the bilateral anterior insula, bilateral dorsal ACC extending into the presupplementary motor area (BAs 6,8,24,32), and the right lateral PFC (i.e., DLPFC and VLPFC; BAs 9,10,44,45,46,47). 45 In this study, our results also present similar activations in several prefrontal cortical areas (such as BAs 8, 9, 10, 6 and 7].…”
Section: Consistency Between Our Results and Those By Fmrisupporting
confidence: 72%
See 2 more Smart Citations
“…44 Another recent fMRI study also reported significant activations in several cortical and subcortical regions when a high-pain cold stimulus was applied to the thenar surface of the right hand. The activated regions included, but were not limited to, the bilateral anterior insula, bilateral dorsal ACC extending into the presupplementary motor area (BAs 6,8,24,32), and the right lateral PFC (i.e., DLPFC and VLPFC; BAs 9,10,44,45,46,47). 45 In this study, our results also present similar activations in several prefrontal cortical areas (such as BAs 8, 9, 10, 6 and 7].…”
Section: Consistency Between Our Results and Those By Fmrisupporting
confidence: 72%
“…In addition, they suggested that the caudate nucleus and PFC play a crucial role in initiation and maintenance of suppression of pain, respectively. 46 Another fMRI study by a separate group also demonstrated the role of the anterolateral PFC in expected and perceived control over pain. 17 Also, a PET-based study of pain reported the influence of DLPFC on pain perception by modulating cortico-subcortical and cortico-cortical pathways.…”
Section: Consistency Between Our Results and Those By Fmrimentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, the insular cortex is described as one of the most consistently activated structures and seems to play a pivotal role within the cortical pain circuitry. Hence, the significance of the insular cortex as a core structure in pain processing has been established [1,9,[11][12][13][14][15][16].…”
Section: Insula-specific Responses Induced By Dental Pain a Proton Mmentioning
confidence: 99%
“…51 Electrical stimulation of the caudate has been shown to provide relief from pain in patients with chronic pain, possibly by inhibiting the activity of the medial thalamus. 52 The specific area in the caudate head identified by the betweengroup contrast (Montreal Neurological Institutes [MNI] coordinates 4, 16, 0) has previously also been implicated in modulation of pain intensity through expectancy 53 and at the onset of effortful suppression of thermally induced pain, 54 indicating that top-down modulation may be at play. However, the brain regions that have previously been implicated in top-down modulation, namely the anterior cingulate cortex and the medial prefrontal cortex, 46,55,56 did not show increased activations.…”
Section: Stress-induced Analgesiamentioning
confidence: 99%